Organization and Methodological Support of Financial Monitoring in an Auditing Firm: New Requirements - LUBENCHENKOО. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2020)
The requirements to implementation of financial monitoring by auditing entities, as specified by the Law of Ukraine “On prevention and counteraction to legalization (laundering) of proceeds from crime, financing of terrorism and financing of proliferation of weapons of mass destruction” from 06.12.2019 No 361-ІХ, enforced on 28.04.2020, are analyzed. The existence of unclear interpretations of some notions in the this Law of Ukraine or heavy financial sanctions that may be imposed on auditing entities call for elaboration and introduction of internal firm documents concerned with financial monitoring. While in the previous edition of the above Law of Ukraine the features of financial monitoring organization were specified for auditing entities in case of rendering certain categories of services to a client (realty transactions; asset management; raising funds to establish legal entities, support to their operation and management, buying and selling of corporate rights), they are not found in the updated edition of this Law of Ukraine. Therefore, auditing entities need to rely upon general norms of the Law of Ukraine in organizing financial monitoring. A series of administrative documents were elaborated for this purpose: the order on assignment of a person responsible for carrying out financial monitoring; the conclusion of business character test for the candidate on the position of the responsible person, the Rules for financial monitoring of an auditing entity, and the monthly fact sheet of the responsible person about the results of carried out measures on financial monitoring. The developed Rules of financial monitoring cover all the regulatory requirements for the implementation of financial monitoring, with the possibility of making change in case of need. The Rules must be informed to the staff of an auditing entity, engaged in rendering auditing and non-auditing services, through the involvement in internal training on financial monitoring issues. Apart from the Rules, it is proposed to supplement the working documents supporting the financial monitoring procedures by the following sections: (i) “Documentary support to financial monitoring of auditing entities”; (ii) “Personnel and personnel training on financial monitoring issues”; (iii) “Documentary support to interactions with the State Service of Financial Monitoring of Ukraine, ministries and administrative departments”, which are supposed to help auditing entities to fully observe the regulatory requirements and avoid heavy financial sanctions on the part of controlling and regulatory bodies.